Keragaman Media dengan Pengetahuan DBD Di Dukuh Gumulan Klaten Tengah Kabupaten Klaten - Besar Tirto Husodo (Interaksi: Jurnal Ilmu Komunikasi, 2012)
Abstract The objective of the study is to analize variety of media used for accessing information about DHF (Dengue Haemorrahagic Fever). The research uses cross sectional approach by intervieving 61 housewifes live at Gumulan village, Klaten, Central Java. The statistic test indicate that there is rellation between the using of medium and interviewee knowledge (p-value is 0.041 and F(count) 4.175). Moreover, there are some variation usage of media as source of information about DHF based on level of education, kinds of interviewee activity, and the variation. Keywords: variation usage media, source of the information,knowledge about DHF